DIGITAL LITERACY CAMPAIGN AND PUBLIC INFORMATION BEHAVIOR CHANGE: A CASE OF OPAC USE - Sherly Rosa Anggraeni; Tsabitah Tifali Dhiyaulhaq; Putri Shofura; Sabrina Bunga Cantika; Yeremia Rizky Paramasatya (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2025)
This study aims to evaluate the effectiveness of a digital literacy campaign based on video and booklet media in improving the public's understanding and skills in using the Online Public Access Catalog (OPAC) at the Malang City Library. The study addresses the gap between OPAC service availability and users' limited digital literacy, which hinders optimal utilization of library technologies. Data were collected from 136 respondents representing diverse demographic backgrounds. A mixed-method pre-test and post-test design was applied to measure changes in knowledge, attitudes, and OPAC use, complemented by thematic analysis of interviews. The results show a significant improvement in users' OPAC knowledge and their ability to conduct independent searches after the campaign. Confidence and perceived ease of use also increase, accompanied by a notable reduction in perceived technical barriers. Qualitative findings strengthen these results by confirming that video and booklet media help simplify OPAC usage and make users more prepared to adopt digital services. Overall, the campaign demonstrates effectiveness as a targeted intervention that supports behavioral change toward technology-based information seeking. These findings highlight the importance of continuous user education, strengthened digital literacy, and accessible guidance materials for sustaining the digital transformation of public library services.